Caracterización de genotipos de frijol (Phaseolus vulgaris) por su resistencia a Thrips palmi (Thysanoptera: Thripidae) - Díaz, J.; Cardona Mejía, César; Bueno Mondragon, J.M. (2003)
To identify sources of resistance to Thrips palmi Karny in dry beans ( Phaseolus vulgaris L.), three field trials were conducted in Pradera (Cauca Valley, Colombia) under heavy natural infestation. In the first trial, 38 genotypes were characterized for resistance to T. palmi in a completely randomized block design. In the other two trials, nine genotypes were used in a split-plot design. In one case, the main plot was fertilization level; while in the other, chemical protection was the main plot. Variation in T. palmi attack was detected in the genotypes tested. Thrip populations showed an aggregate pattern of distribution and had a significant effect on damage levels to plants. Damage negatively affected reproductive adaptation and yield plants. Genotypes Brunca, BH 21134-5, EMP 486, BAT 477, FEB 115 y BH 21134-60 showed resistance to Thrips in the experiments. Fertilization levels did not have an effect on resistance expression. Losses due to Thrips damage ranged from 11,9% to 65,1%. FEB 115, BH 21134-5, EMP 486, BH 21134-60 and Brunca were below the average susceptibility index of the experiment; genotypes with low susceptibility indexes may have tolerante to damage and suffer lower losses. Further work is needed in order to elucidate the mechanisms of resistance to Thrips in resistant genotypes.